Impact of rethrical insecurity on the development of argumentative strategy. - FADHLOUNE, Ouarda (Journal of Human Sciences, 2022)
The present study aims at showing how rethorical insecurity and reliance on heavy correction affect the formation of arguments and thus the argumentative strategy adopted by the speaker. Data collection is based on one debate, drawn from a didactic sequence that was filmed during the academic year 2016. The sample in this study belongs to second year university students at University. The theoretical foundation within which this piece of research is conducted are the works of Marie Françoise Chanfrault Duchet and Vigostsky.